The importance of taking a comprehensive perspective in the strategic planning of human resource development to address the lack of human capacity development - Abu Zeid, Mu'tasim Hussein (Journal of Economic, Administrative and Legal Sciences, 2017)
This paper aimed to highlight the importance of strategic planning for human resources development in the treatment of human capacities and competencies in light of the global and domestic challenges, have been some of the terminology and concepts related to the study review, as well as to clarify some aspects of the study, was reached on the results and a summary was clarified through which the need to adopt a comprehensive system for human resources development in the framework of the national strategy to achieve the requirements of the human side, especially the development of national human capacity. This study is trying to contribute to the foundation for the study aims to lay the foundations to build a comprehensive system of human resource development in Sudan.